Inpatient Care for Elderly Suicide Survivors: Nurse-Led Mindfulness-Based Cognitive Therapy - Li, Dandan; Fan, Mingsi; Bian, Hailei; Ni, Li (Alpha psychiatry : (Online), 2024)
The aim was to analyze the effects of nurse-led mindfulness-based cognitive therapy (MBCT) in hospitalized elderly suicide survivors. The data of middle-aged and elderly suicide survivors in the medical system and nursing records of our hospital from January 2018 to August 2023 were retrospectively collected. The patients were divided into conventional group and MBCT group according to whether they actively received MBCT. The general demographic data of the patients and the changes in the scores of Suicidal Ideation Scale (SSI), Beck Hopelessness Scale (BHS), Patient Health Questionnaire 15 (PHQ-15), and Geriatric Depression Scale (GDS-15) at admission and 3 and 6 months of follow-up were collected. Propensity score matching was used to balance the baseline data of the 2 groups. Multiple logistic regression analysis was used to determine the effect of the inpatient care program on each score. A total of 160 patients were included in the study, including 100 patients in the MBCT group and 60 patients in the conventional group. There was no significant difference in baseline data between the 2 groups after matching ( > .05). Suicidal Ideation Scale score, BHS score, PHQ-15 score, and GDS-15 score in MBCT group were lower than those in conventional group at 6 months of follow-up ( < .05). At the same time, multiple logistic regression analysis showed that the intervention program was the main factor affecting the SSI (OR = 1.538, = .010), BHS (OR = 1.614, = .006), PHQ-15 (OR = 1.797, = .001), and GDS-15 scores (OR = 1.642, = .004) at 6 months of follow-up. The application of nurse-led MBCT in hospitalized elderly suicide survivors may reduce suicidal ideation, hopelessness, and depression and improve physical symptoms.